Fatores associados à transmissão vertical da infecção pelo HIV e manifestações clínicas em crianças notificadas no Hospital Infantil Nossa Senhora da Glória, 2005-2008 - Dias, Carolina Frizzera (2011)
Introduction: The main indicator of monitoring the reduction on HIV infection in children is the incidence rate of AIDS incidence in children under five years ols. Objectives: Describe the profile of children exposed to HIV attending the reference center for AIDS in chldren at The Hospital Infantil Nossa Senhora da Glória (HINSG) and determine the vertical transmission rate and clinical signs and simptoms among the infected ones. Methods: Descriptive study in children exposed to HIV infection by vertical transmission attending a pediatric public hospital in Vitoria (ES) from January 2005 to December 2008. A questionnaire including epidemiological and clinical data of mother and child was applyed. Associations between HIV positive and negative cases were tested using chi-square test. Odds Ratio and confidence intervals were calculated and multivariate logistic regression was used. Results: Two hundred and twenty-one children (97.8%) were exposed to HIV during pregnancy or childbirth. A total of 47 (21.3%) children were diagnosed with AIDS; 25 (53.2%) have already entered service with the diagnosis and 22 (44.8%) became positive during follow-up. A frequencia de infecção de HIV foi de 21,3% (IC 95% 15,9%-26,7%). One hundred and ninety-three (87.3%) children were admitted in the hospital in their first year of life, 51.1% vs. 97.1% (p <0.001), when comparing AIDS cases with those with negative serology. The frequency of HIV infection was 21.3% (IC 95% 15.9%-26.7%). Regarding children s mothers included in the study, diagnosis of HIV infection was performed before pregnancy in 97 (43.3%) cases, in 56 (25.0%) during the prenatal period, and in 59 (26,4%) at birth or after delivery. In 12 cases (5.4%), mode of maternal diagnosis was unknown. Among factors independently associated with vertical transmission of HIV: having entered the service before the first year of life [OR = 0.08 (0.17 to 0.37)], be alive [OR = 0.12 (0, 31 to 0.47)] and have received complet prophylaxis [OR = 0.29 (0.09 to 0.97)] were protective factors while being born by vaginal delivery [OR = 4.45 (1.47 - 13.47)] was a risk factor for HIV infection. Regarding clinical symptms in children, the most common was anemia for more than 30 days (65.9%), followed by wasting syndrome (59.6%) and bacterial meningitis, pneumonia or sepsis (57.4%). Sixteen children (32% of cases) were classified in category C3, the most serious of all. Conclusions: The results showed high frequency of HIV in children. Received the omplet prophylaxis and joining the service less than one year of life were protectors factors. Being born through vaginal delivery was risk factor for transmission. Most children had moderate to severe manifestations of AIDS, demonstrating importance of constant monitoring of prophylactic measures for mother and child for controling HIV among children.